Pengolahan Limbah Cangkang Kerang Mutiara (Pinctada Maxima) Sebagai Adsorben Logam Berat Fe - Susi Rahayu; Siti Alaa; Dewi Handayani; Dian W Kurniawidi (Universitas Muhammadiyah Mataram, 2022)
Fe is a type of heavy metal that can cause damage to the environment and health. If the concentrations of Fe are more than 1 mg/L, it can lead to toxic effects to the human body. The level of Fe contamination in the environment needs to be controlled to diminish hazardous effects. This can be conducted by modifying a smart material to adsorb the Fe metal. The material modification was carried out by isolating pearl oyster shells (Pinctada maxima) into chitosan as Fe metal adsorbent. The main aim of this research is to identify the ability of chitosan to soak Fe up. To obtain chitosan material, the pearl shells were isolated through 3 stages, namely deproteination, demineralization, and deacetylation. The isolated chitosan powder was identified the typical group forming chitosan using FTIR and the yield of each isolation process was calculated. Meanwhile, the ability of chitosan to adsorb Fe metal was identified through testing using AAS. The results of the calculation of the yield of the chitosan isolation process showed a decrease in mass at each stage. Until the final stage, the powder yield decreases to 32.17% from the initial mass used. In addition, the FTIR results also figure out that chitosan was successfully synthesized in the presence of the OH functional group at a wave number of 3434.660 cm-1 and the NH2 functional group at a wave number of 1626.110 cm-1 with a degree of chitosan deacetylation of 80.534%. It is clear from the results of AAS where the highest adsorption capacity is 33,262 mg/g with an adsorption efficiency of 99,788%. Therefore, the pearl shells have been successfully adjusted into chitosan. Where chitosan is one of the excellent biomaterials to absorb the heavy metal.